2018
DOI: 10.1103/physrevd.98.054509
|View full text |Cite
|
Sign up to set email alerts
|

QCD phase diagram in a magnetic background for different values of the pion mass

Abstract: We investigate the behavior of the pseudo-critical temperature of N f = 2+1 QCD as a function of a static magnetic background field for different values of the pion mass, going up to mπ ≃ 660 MeV. The study is performed by lattice QCD simulations, adopting a stout staggered discretization of the theory on lattices with Nt = 6 slices in the Euclidean temporal direction; for each value of the pion mass the temperature is changed moving along a line of constant physics. We find that the decrease of Tc as a functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 204 publications
(146 reference statements)
7
67
1
Order By: Relevance
“…Results supporting IMC were also obtained by further lattice simulations [10][11][12]. It was then believed that MC and IMC corresponded to T c being respectively an increasing or decreasing function of B, but a recent study has shown that as the pion mass is increased, the behavior near T c crosses over from IMC to MC, while T c remains a decreasing function of B all along [13].…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Results supporting IMC were also obtained by further lattice simulations [10][11][12]. It was then believed that MC and IMC corresponded to T c being respectively an increasing or decreasing function of B, but a recent study has shown that as the pion mass is increased, the behavior near T c crosses over from IMC to MC, while T c remains a decreasing function of B all along [13].…”
Section: Introductionmentioning
confidence: 69%
“…6 of Ref. [13]) for comparison. While the different scale-setting procedure obviously leads to quantitatively different results from ours, the qualitative behaviors match nicely.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations